Association of eating behaviors, lifestyle, and maternal education with adherence to the Mediterranean diet in Spanish children. (1st November 2018) - Bawaked, Rowaedh Ahmed; Gomez, Santiago Felipe; Homs, Clara; Casas Esteve, Rafael; Cardenas, Gabriela; Fíto, Montserrat; Schröder, Helmut
Abstract: Background: The Mediterranean diet serves as a proxy of a high-quality diet. Although several factors are known to affect a child's ability to follow a high-quality diet, no prospective data are available on factors that influence adherence to a Mediterranean diet among children. Our objective was to investigate the association of Mediterranean diet adherence with eating behaviors, lifestyle habits, and maternal education in a prospective cohort of children. Methods: The present prospective cohort analysis included 1639 children aged 8–10 years. The study was carried out during two academic years, 2012/2014, with an average follow-up of 15 months. Eating behaviors, physical activity, and adherence to Mediterranean diet were estimated by the Dutch Eating Behavior Questionnaire for Children, the Physical Activity Questionnaire for Children, and the KIDMED index, respectively. Results: Multivariate linear regression analysis adjusted for sex, age, maternal education, baseline adherence to the Mediterranean diet, and intervention group revealed a significant (p < 0.01) inverse association of external eating and screen time with adherence to the Mediterranean diet at follow-up (mean of 15 months). The opposite association was found for meal frequency and physical activity (p < 0.02). A high level of maternal education increased the odds of a child's high adherence to the Mediterranean diet (OR = 1.56 CI 1.13; 2.14) compared to peers whose mothers had only a primary education. Conclusions: Screen time, physical activity, meal frequency, and external eating predict adherence to the Mediterranean diet independently of baseline diet quality. Maternal education level is an important prospective determinant for the adherence to the Mediterranean diet. Trial registration number: ISRCTN68403446.